3D Formation Control of Autonomous Vehicles Based on Null-Space - Rosales, Claudio Dario (2016)
This paper proposes a new algorithm for controlling a formation of multiple autonomous aerial vehicles based on multiple control objectives. The strategy includes using the null space of a Jacobian matrix to achieve the different control objectives in a non-conflicting way. The mission is split into two elementary tasks, with suitable command references generated for each robot. The commands for each task are combined through a hierarchical method by using the projection of commands onto the null space. The incorporation of ground vehicles in the control scheme is also considered, thus extending the proposed scheme for controlling heterogeneous formations. The stability analysis of the control system shows that such a system is asymptotically stable, and experimental results validate the proposed control system.